Isolation of Gluconacetobacter spp. in different soil types - Santos, Carla Cristiane Rocha dos; Perin, Liamara; Baldani, José Ivo; Reis, Veronica Massena (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to improve the immunocapture method for the application to soil samples containing high levels of clay particles and to utilize it for the isolation of Gluconacetobacter diazotrophicus strains from soil cultivated with sugarcane and coffee. The immunocapture technique was applied successfully for isolation of bacterium from soil samples. The modified immunocapture technique with Al2(SO4)3 allowed the application of the method using clayed soil samples by the flocculation of the suspended clay. It proved to be effective for isolation of G. diazotrophicus inoculated in sterile sandy and clay soils five days after inoculation. The maximum sensitivity of the method to isolate G. diazotrophicus cells, using pure culture, was 103 cells mL-1. The modification of the technique allows the capture of Gluconacetobacter spp. from soil samples near the coffee plants but not from sugarcane soils.